Mathematical modeling of multicomponent catalytic processes of petroleum refining and petrochemistry; Reviews in Chemical Engineering; Vol. 37, iss. 1 - Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Dolganova I. O. Irena Olegovna; Belinskaya N. S. Natalia Sergeevna (2021, 2021)
Title screen